Gut content analysis confirms the feeding plasticity of a generalist fish species in a tropical river - Igor David Costa; Ronaldo Angelini (Acta Limnologica Brasiliensia, 2020)
Abstract Aim In this paper, we compared the diet composition of the South American silver croaker, Plasgioscion squamosissimus in preserved and impacted areas (agrarian land use) of an Amazonian river. Our objective was to quantify the plasticity in diet across different habitats and evaluate the importance of a carnivorous generalist species as an environmental indicator based on its feeding variation. Methods We analysed the stomach contents of 135 individuals and compared the trophic level of P. squamosissimus and the source of ingested food items in the impacted and non-impacted habitats. Results The trophic level values in both areas were similar. In both areas, P. squamosissimus used a wide variety of food items, consuming mainly fish and invertebrates of autochthonous origin. However, in terms of composition of food items, small pelagic fish and autochthonous items were more frequently consumed in the preserved area, while in the impacted area fish and benthic invertebrates were predominant in the diet. Conclusions Our gut analysis suggests plasticity in P. squamosissimus diet across varying areas, which point to the ability of P. squamosissimus to modify their diet in the impacted situation, utilizing more benthic material on impacted area in order to maintain a similar trophic position.